Genesis, Procedures, Attrition Rate and Major Reasons for Missing Measurement Session by the Study Participants in the Ellisras Longitudinal Study - Phuti Makgae; Betty Sebati; Hlengani Siweya; Kotsedi Monyeki (MDPI AG, 2020)
The noncommunicable diseases' (NCDs) profile is changing rapidly from one country to another. A well-formulated cohort study in Africa could answer major questions relating to the changing profile of NCDs risk in Africa. The aim of the present study was to outline the genesis, procedures, attrition rate and major reasons for study participants to miss measurement sessions in the Ellisras Longitudinal Study (ELS). Method: The ELS followed multiple longitudinal designs comprising repeated measurements in more than one cohort with overlapping ages. Age cohort and time of measurement effects could be identified. A cluster random sampling method was used to sample 2255 participants (1201 males and 1054 females), aged 2 to 10.9 years at baseline (November 1996). Information on lifestyle (tobacco and smoking, alcohol intake, physical activity and socioeconomic status) and biological risk factors for NCD and educational achievements were collected over time. The participants were followed 17 times over the past 25 years with measurements (blood pressure and anthropometry) collected twice during the first consecutive 8 years to account for growth dynamics and other health-related variables. The attrition rate for ELS sample for boys (14%-27.3%) was significantly (p < 0.05) higher than girls (7.9%-18.6%) from May 1999 to November 2003. There was a significant (p < 0.05) increase (25.3%-70.3%) in attrition rate from November 2009 to December 2015. The ELS participant migration to urban areas provided a unique opportunity to investigate the effect of urban life on these rural young adults given the previous data collected on the same subjects at a younger age (3-10 years at baseline in 1996). Conclusion: A well-formulated ELS study in Africa could answer major questions relating to the changing magnitude of NCDs risk factor profiles in Africa.